2010
DOI: 10.1007/s12010-010-9104-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased In Vitro Lysosomal Function in Oxidative Stress-Induced Cell Lines

Abstract: Exposure of mammalian cells to oxidative stress alters lysosomal enzymes. Through cytochemical analysis of lysosomes with LysoTracker, we demonstrated that the number and fluorescent intensity of lysosome-like organelles in HeLa cells increased with exposure to hydrogen peroxide (H₂O₂), 6-hydroxydopamine (6-OHDA), and UVB irradiation. The lysosomes isolated from HeLa cells exposed to three oxidative stressors showed the enhanced antimicrobial activity against Escherichia coli. Further, when lysosomes that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 21 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…This fact became the rationale for the hypothesis of reduced lysosomal functional activity in senescence, which results in the accumulation of “wrong” proteins and entire cellular structures such as defective mitochondria . At the same time, some experiments demonstrated an elevated LysoTracker fluorescence after different stress conditions and confirmed the increased antimicrobial and apoptotic activity of isolated lysosomes . Thus, the detected increase in the LysoTracker fluorescence may be evidence of enlargement of lysosomal compartment in senescence, which is the cell response on the progressive increase in the number of defective structures.…”
Section: Discussionsupporting
confidence: 53%
“…This fact became the rationale for the hypothesis of reduced lysosomal functional activity in senescence, which results in the accumulation of “wrong” proteins and entire cellular structures such as defective mitochondria . At the same time, some experiments demonstrated an elevated LysoTracker fluorescence after different stress conditions and confirmed the increased antimicrobial and apoptotic activity of isolated lysosomes . Thus, the detected increase in the LysoTracker fluorescence may be evidence of enlargement of lysosomal compartment in senescence, which is the cell response on the progressive increase in the number of defective structures.…”
Section: Discussionsupporting
confidence: 53%
“…Lysosomal enzymes are easily release from exposed on oxidative stress lysosomes. It has been shown that oxidative stress causes an increased level of reactive oxygen species and that apoptotic cell death may be induced under severe oxidative stress [17].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms involved in the activation of autophagy by ROS include inhibition of mTOR activity [12], activation of extracellular regulated kinase (ERK) and/or c-Jun N-terminal kinase [13, 14], nuclear translocation of the high-mobility group box 1 Protein, as shown upon the activation of autophagy by Apogossypolone [15], increase in Beclin 1 expression, and inhibition of the cysteine protease Atg4 activity [16]. However, while these mechanisms mainly focus on the regulation of the formation of autophagic vacuoles, ROS have also been shown to affect lysosomes [17]. Lysosomes and lysosomal proteases play important roles in the final stages of autophagy, such as the fusion of lysosomes with autophagosomes forming autolysosomes followed by proteolytic degradation of the engulfed molecules by lysosomal proteases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, lysosomal numbers, composition and function are sensitive to various external and internal stresses including redox stress [18]. For example, exposure of HeLa cells to H 2 O 2 , 6-hydroxydopamine (6-OHDA), and UVB irradiation led to an increase in lysosome numbers as well as lysosomal activity [17]. …”
Section: Introductionmentioning
confidence: 99%